Pengelolaan Kurikulum Operasional Madrasah di MAN 1 Kota Bekasi - Apriyanti Wulandari; Husen Hasan Basri; Saimroh Saimroh (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2023)
Â Abstract The learning load for madrasas is greater because it accommodates the curriculum program set by the Ministry of Education, Culture, Research and Technology plus a curriculum program related to Islamic religious content set by the Ministry of Religion. This high learning load is carried out in accordance with regulations from the center without any adjustments according to the resources and orientation of education services in each madrasah. This study aims to examine curriculum management which includes planning, implementation, and evaluation at MAN 1 Bekasi City. The results of the research found that curriculum management at MAN 1 Bekasi City was still focused on implementation that had not been well planned and evaluation based on problems. The operational curriculum that has been prepared does not yet describe the practice of educational services carried out at MAN 1 Bekasi City. Input the results of the study to MAN 1 Bekasi City as a proposal to improve curriculum documents.